LOW PREVALENCE OF CHLAMYDIA TRACHOMATIS INFECTION IN WOMEN FROM SOUTHERN NIGERIA - O., Adesiji Y; I., Iyere S; J., Ogah I (Journal of Health and Allied Sciences NU, 2015)
Chlamydia trachomatis infections are the most common bacterial cause of sexually transmitted diseases (STDs) in the world. However, most Nigeria health care facilities do not screen for Chlamydia antigen in gynaecological and general out-patient clinics. This study was to document the prevalence of Chlamydia trachomatis infection in patients attending Family Planning Clinics and Gynaecology clinics in Southern Nigeria. Endocervical swabs were collected from a hundred and forty patients and were screened using Chlamydia Rapid Test Device –Swab / Urine (Interchemical Ltd. China). Out of 140 patients screened, 1 (0.7%) was positive for Chlamydia trachomatis antigen. There seem to be an association between Chlamydia infection and abortion thus screening for chlamydia trachomatis infection in asymptomatic patients to prevent the adverse consequences. This study presents an update in Chlamydia trachomatis in the Southern part of Nigeria.
Keywords: Chlamydia trachomatis; prevalence; women; southern; Nigeria